2023
DOI: 10.3390/antibiotics12030544
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis Reveals New Integrative Conjugal Elements and Transposons in GBS Conferring Antimicrobial Resistance

Abstract: Streptococcus agalactiae or group B streptococcus (GBS) is a leading cause of neonatal sepsis and increasingly found as an invasive pathogen in older patient populations. Beta-lactam antibiotics remain the most effective therapeutic with resistance rarely reported, while the majority of GBS isolates carry the tetracycline resistance gene tet(M) in fixed genomic positions amongst five predominant clonal clades. In the UK, GBS resistance to clindamycin and erythromycin has increased from 3% in 1991 to 11.9% (cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 43 publications
(70 reference statements)
2
10
0
Order By: Relevance
“…The few isolates showing the L phenotype coherently harbored the lsa(C) gene and belonged exclusively to CC19 expressing serotype III-1. On the other hand, the high rate of resistance to tetracycline was largely mediated by tet(M) and to a lesser extent by tet(O) , which was largely in agreement with previously published studies ( Bergal et al., 2015 ; Jin et al., 2022 ; Rodgus et al., 2022 ; Khan et al., 2023 ). Sequence analysis linked gentamicin resistance with the presence of the gene encoding the bifunctional aminoglycoside-modifying enzyme AAC(6’)-APH(2’), and also identified other genes associated with resistance to kanamycin and streptomycin (i.e., ant(6)-Ia , aph(3’)-III , and aadE ) in a small proportion of isolates (16.85%, n = 15/89), mainly belonging to CC17 and CC12.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The few isolates showing the L phenotype coherently harbored the lsa(C) gene and belonged exclusively to CC19 expressing serotype III-1. On the other hand, the high rate of resistance to tetracycline was largely mediated by tet(M) and to a lesser extent by tet(O) , which was largely in agreement with previously published studies ( Bergal et al., 2015 ; Jin et al., 2022 ; Rodgus et al., 2022 ; Khan et al., 2023 ). Sequence analysis linked gentamicin resistance with the presence of the gene encoding the bifunctional aminoglycoside-modifying enzyme AAC(6’)-APH(2’), and also identified other genes associated with resistance to kanamycin and streptomycin (i.e., ant(6)-Ia , aph(3’)-III , and aadE ) in a small proportion of isolates (16.85%, n = 15/89), mainly belonging to CC17 and CC12.…”
Section: Discussionsupporting
confidence: 92%
“…Of particular concern was the high proportion of isolates with reduced susceptibility to macrolides and lincosamides, which are the antibiotics of choice for the treatment of GBS infections in patients with penicillin allergies. Here also, the molecular mechanisms of resistance to these antibiotics were consistent with those previously described for this species ( Bergal et al., 2015 ; Jin et al., 2022 ; Rodgus et al., 2022 ; Khan et al., 2023 ). Phylogenetic analysis showed that resistance to macrolides and lincosamides was not necessarily linked to the expansion of certain CCs but was distributed across all detected CCs.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The high level of resistance to gentamicin is due to the production of bifunctional APH (2')-ACC(6) enzymes, which determine the reduction of synergism between all aminoglycosides (except streptomycin and arbekacin) and beta-lactams and glycopeptides, regardless of MIC levels (Guo et al, 2018;Dobrut et al, 2022). GBS resistance to tetracycline is most often caused by two mediated genes, tet(M) and tet(O), which are transmitted mainly by transposons (Ali et al, 2020;Khan et al, 2023). The resistance of GBS to fluoroquinolones is due to the presence of mutations in the gyrA and parC genes, therefore, in the bacteriological laboratory, the phenotypic definition of resistance to this group of antibacterial drugs is determined by sensitivity to norfloxacin as a screening test.…”
Section: Introductionmentioning
confidence: 99%